Bandung City's Parallel Diplomacy in Promoting Tegep Boots Fashion UMKM Products in Italy 2023 - Mohammad Raihan Anwari; Windy Dermawan (Badan Penerbit STIEPARI Press, 2025)
The development of international relations issues has made sub-state actors such as cities, states, and provinces enter international activities. With the rise of these issues, it is also based on the concept of decentralization and paradiplomacy and local governments with their autonomy rights can build cooperative relationships with governments at the same level globally. In carrying out the realm of promoting MSMEs, the City of Bandung is assisted by the Department of Trade and Industry. With the aim of this research, namely to find out how the parallel diplomacy process is carried out by the City of Bandung in promoting MSME Tegep Boots. This research uses a qualitative method with data collection techniques through interviews and also uses literature studies. In the results of the study, it was found that the City of Bandung actually carried out an elaboration with the City of Garut in promoting MSME Tegep Boots. So in terms of parallel diplomacy carried out by the actors, it actually proves that there is cooperation carried out by subnational actors from both the City of Bandung and the City of Garut with social actors, namely MSME Tegep Boots. In conducting a promotion of Tegep Boots UMKM in Italy, especially at the Lineapelle the International Leather Fair event, it turns out that the ones who play a big role are actually from Garut City and also Tegep Boots UMKM, and also most of the international events in promoting Tegep Boots, Tegep Boots actually also carries out many of these activities independently because units from Bandung City such as its government cannot only focus on Tegep Boots UMKM continuously.